Birth order is associated with caries development in young children: a register-based cohort study - A. Julihn; F. C. Soares; U. Hammarfjord; A. Hjern; G. Dahllöf (BMC, 2020)
Abstract Background Birth order has been shown to affect the health of the child; less is known, however, about how birth order affects caries development in children. Thus, the present study investigated the association between birth order and dental caries development in young children. Methods This retrospective registry-based cohort study included all children born in 2000-2003 who were residing in Stockholm County, Sweden, at age 3 years (n = 83,147). The study followed the cohort until subjects reached 7 years of age. Children with registry data on dental examinations and sociodemographic characteristics at ages 3- and 7 years constituted the final study cohort (n = 65,259). The outcome variable was "caries increment from age 3- to 7 years" (Δdeft > 0) and the key exposure, "birth order", was divided into five groups. A forward stepwise logistic binary regression was done for the multivariate analysis with adjustments for sociodemographic factors. Results At age 3 years, 94% had no fillings or manifest caries lesions. During the study period, 22.5% (n = 14,711) developed dental caries. The final logistic regression analysis found a statistically significant positive association between birth order and caries increment. Further, excess risk increased with higher birth order; with the mother's first-born child as reference, risk for the second-born child was OR 1.17, 95% CI = 1.12-1.23; for the third-born child, OR 1.47, 95% CI = 1.38-1.56; for the fourth-born child, OR 1.69, 95% CI = 1.52-1.88; and for the fifth-born or higher birth-order child, OR 1.84, 95% CI = 1.58-2.14. Conclusions These findings show that birth order influences caries development in siblings, suggesting that birth order can be regarded as a predictor for caries development in young children. This factor may be helpful in assessing caries risk in preschool children and should be considered in caries prevention work in young children with older siblings.